STUDY ON CONSUMER ACCEPTANCE OF CATFISH (Pangasius hypophthalmus) BALL WITH THE ADDITION OF YELLOW BUR HEAD (Limnocharis flava) POWDER - Syahputri, Erlina Windi; Sukmiwati, Mery; N. Ira Sari, N. Ira Sari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThis research was intended to find out the consumer acceptance of catfish (Pangasius hypophthalmus) ball with addition yellow bur head (Limnocharis flava) powder. The method in this research was an experimental method on processing ofcatfish ball with addition of yellow bur head powder.The method used was experimental method with Completely Randomized Design (CRD) consisting of 4 treatment levels ie B0(without addition of yellow bur head powder), B1(addition 3% yellow bur head powder), B2(addition 6%yellow bur head powder) and B3(addition 9% yellow bur head powder). Based on the result of this research, it was determined that B1was the best treatment which organoleptic value of appearance 7.15 (95% with 76 panelists) which criteria was greenish, aroma 7.32 (91.25% with 73 panelists) which criteria was typical aroma of catfish ball and seasoning aroma was strong, taste 7.19 (91.25% with 73 panelists) which criteria was unique taste of catfish with addition of yellow bur head powder, and texture 7.46 (91.25% with 73 panelists) which criteria was smooth and soft fibers; with chemical values of moisture, ash, fiber, protein content, and total colonial bacteriawere 56.55%, 2.02%, 3.33%,16,50% and 9.4 x 104sel/gram, respectively. Keywords: Pangasius hypophthalmus, Limnocharis flava, Catfish ball